Integrating Social Empowerment and Membrane Technology for Clean Water Access in a Rural Indonesian Community Case Study in Nganti Village, Bojonegoro - Handono, Setiyo Yuli; Wibisono, Yusuf; Nugroho, Wahyunanto Agung; Arif, Chusnul (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
Human resilience is related to the availability of natural resources, such as water, which is developed through community empowerment and technology. Nganti Village, Bojonegoro is one of the villages that is vulnerable to the availability of clean water for daily consumption. So, this research aims to (1) analyze the problems and potential of water sources that are not utilized by the Nganti community, (2) analyze community strategies in dealing with water problems, and (3) simulate alternative membrane technology based on community empowerment. This research used a combined approach, quantitative and qualitative, involving key informants, including the Village Head, Head of the Clean Water Association, Ngraho Sub-district Head, and Community Leaders, in addition to a survey of 40 Nganti-Ngraho residents. Data analysis is descriptive statistical and qualitative. The water quality of a spring in Nganti Village shows that the water is not suitable for drinking, washing and latrines (MCK) due to the high content of iron and other metals. Meanwhile, the community's strategy is to use water reservoirs as an alternative water source and introduce membrane technology through community empowerment activities.